2008
DOI: 10.1074/jbc.m707736200
|View full text |Cite
|
Sign up to set email alerts
|

State-dependent Access of Anions to the Cystic Fibrosis Transmembrane Conductance Regulator Chloride Channel Pore

Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR) Cl ؊ channel is gated by intracellular factors; however, conformational changes in the channel pore associated with channel activation have not been identified. We have used patch clamp recording to investigate the state-dependent accessibility of substituted cysteine residues in the CFTR channel pore to a range of cysteine-reactive reagents applied to the extracellular side of the membrane. Using functional modification of the channel current-volt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
46
6

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 22 publications
6
46
6
Order By: Relevance
“…The channel pore architecture has been experimentally probed using cysteine mutants and thiol-reactive reagents to determine the accessibility of particular sites in the pore. Taken together, these studies are strongly supportive of the Sav1866-based homology models (Zhang et al 2005;Fatehi and Linsdell 2008;Alexander et al 2009). They show a pore that is wide on the extracellular side and becomes more inaccessible to molecular probes, especially anionic probes, moving toward the cytoplasmic surface.…”
Section: Dynamics Intrinsic To Cftr Function and Stabilitysupporting
confidence: 62%
“…The channel pore architecture has been experimentally probed using cysteine mutants and thiol-reactive reagents to determine the accessibility of particular sites in the pore. Taken together, these studies are strongly supportive of the Sav1866-based homology models (Zhang et al 2005;Fatehi and Linsdell 2008;Alexander et al 2009). They show a pore that is wide on the extracellular side and becomes more inaccessible to molecular probes, especially anionic probes, moving toward the cytoplasmic surface.…”
Section: Dynamics Intrinsic To Cftr Function and Stabilitysupporting
confidence: 62%
“…A conformational change of this sort would be consistent with the state-dependent reactivity of the F337C and T338C CFTRs observed in the current study. The MsbAbased model described by Mornon et al (2009) also suggests that the side chain of Arg334 protrudes into the external aqueous environment; when Arg334 is mutated to a cysteine 2 The findings presented here regarding the state-dependent reactivity of engineered cysteines are at odds with previous reports (Wang and Linsdell, 2012;Fatehi and Linsdell, 2008). Wang and Linsdell (2012) Ϫ and suggested that the reaction of an engineered cysteine at position 338 with externally applied reagents was favored in the closed state.…”
contrasting
confidence: 57%
“…We observed reaction rates for MTSES Ϫ with T338C/wt and T338C/E1371Q CFTRs that were similar to those observed by Beck et al (2008) (data not shown), which supports the idea that the T338C CFTR reacts in the open state. Fatehi and Linsdell (2008) reported, contrary to our findings, that reactions of MTSES Ϫ and [Au(CN) 2 ] Ϫ with a cysteine at position 334 were favored in the activated state of the channel. Cells expressing the R334C CFTR were preincubated with MTSES Ϫ with and without an activating cocktail of forskolin and IBMX, and the reaction, which was inferred on the basis of changes in the rectification ratio of the CFTR I-V curve, was observed only with cells exposed to the activating cocktail.…”
contrasting
confidence: 56%
See 2 more Smart Citations